Kinetic analysis and dielectric properties of tyrosine-based tripeptide side groups carrying novel methacrylate polymers - Biryan, Fatih; Caliskan, Eray; Koran, Kenan (Springer, 2022)
In this study, dipeptide synthesis was performed with tyrosine and methionine in the presence of triazine. Then, tripeptides were prepared by the same method with valine and alanine amino acids. New methacrylate monomers were synthesized by the reaction of phenolic OH of tyrosine in tripeptides and methacryloyl chloride. Polymerization of monomers was carried out using AIBN initiator at 70 degrees C according to free radical polymerization method. The structural characterization of the obtained materials was performed using FT-IR, H-1-NMR, C-13-NMR spectroscopic techniques. The thermal behavior of homopolymers with tripeptide side groups was determined by DTA and TGA methods. The glass transition temperatures of the polymers containing valine and alanine were determined as 225 degrees C and 214 degrees C, respectively. From the TGA results measured at different heating rates (5, 10, 20, 30, and 40 degrees C min(-1)), the average activation energies of valine and alanine-containing polymers were calculated as 87.64 and 115.92 kJ mol(-1) based on the Flynn-Wall-Ozawa (F-W-O) method. The dielectric constant, dielectric loss factor, and ac conductivity values of the polymers were determined as a function of frequency (between 100 Hz and 100 kHz) with an impedance analyzer at room temperature. The dielectric constants of valine and alanine containing homopolymers were calculated as 8.64 and 5.12 at 1 kHz constant frequency and alternative current conductivity of 5.27 x 10(-09) S cm(-1) and 3.06 x 10(-09) S cm(-1), respectively.
Keywords: Dielectric properties; Homopolymer; Thermal analysis; Tripeptide; Synthesis